1992
DOI: 10.1002/pssa.2211320225
|View full text |Cite
|
Sign up to set email alerts
|

Praseodymium Zircon Yellow

Abstract: The properties of praseodymium zircon yellow and of corresponding samples with a nominal substitution of Ce4+ for Zr4+ as well as Ti4+ for Si4+ (system ZrSiO,: Pr,Ce,Ti,) are investigated by X-ray methods, diffuse reflectance, and vibrational spectroscopy. From the present results follows that the ZrSiO, structure does not tolerate a significant substitution level on either Zr4+ or Si4+ regular lattice positions by the larger foreign ions Ce4+, Pr4+, and Ti4+. Thus, the yellow colour is the result of the usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It should be added that doped synthetic ZrSiO 4 of various colouration is used as high-temperature stable and chemically inert pigments. These include, for instance, yellow Pr 3+ -doped ZrSiO 4 (Stiebler et al, 1992;Del Nero et al, 2004), 'lemon'-yellow Tb 3+ -doped ZrSiO 4 (Kar et al, 2004), blue V 4+ -doped ZrSiO 4 (Demiray et al, 1970;Niesert et al, 2002;Pyon et al, 2011) and pink-to-red Fe-doped ZrSiO 4 (Cappelletti et al, 2005). It is, however, well known that the colours of natural zircon have different causes than those of the synthetic pigments, the latter of which contain dopant levels several orders of magnitude above the concentrations of the same elements in natural zircon.…”
Section: Introductionmentioning
confidence: 99%
“…It should be added that doped synthetic ZrSiO 4 of various colouration is used as high-temperature stable and chemically inert pigments. These include, for instance, yellow Pr 3+ -doped ZrSiO 4 (Stiebler et al, 1992;Del Nero et al, 2004), 'lemon'-yellow Tb 3+ -doped ZrSiO 4 (Kar et al, 2004), blue V 4+ -doped ZrSiO 4 (Demiray et al, 1970;Niesert et al, 2002;Pyon et al, 2011) and pink-to-red Fe-doped ZrSiO 4 (Cappelletti et al, 2005). It is, however, well known that the colours of natural zircon have different causes than those of the synthetic pigments, the latter of which contain dopant levels several orders of magnitude above the concentrations of the same elements in natural zircon.…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al first reported the existence of Pr‐doped zircon pigment in 1952. The mechanism underlying the formation of Pr‐ZrSiO 4 , the locations of Pr, as well as its valence states, and the types and uses of mineralizer have been studied in detail by many researchers. The reported methods of synthesis for Pr‐ZrSiO 4 pigment include solid‐state reaction, sol‐gel, nonhydrolytic sol‐gel and hydrothermal methods .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] and references therein) and of the colour of zircon crystals and powders [3,4]. These studies contributed to the understanding of these materials for their possible use as lasers and television phosphors (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These studies contributed to the understanding of these materials for their possible use as lasers and television phosphors (see Refs. Some of these ions together with Fe 3+ are used in the manufacture of pigments (V 4+ , blue, Pr 3+ , yellow [4,6] and Fe 3+ , pink [3]). Much less has been published on the spectra of 3d ions in these systems.…”
Section: Introductionmentioning
confidence: 99%